Association between carotid intima media thickness and metabolic syndrome - G., Abhishek T.; Darshan, Arathi; Appajigol, Jayaprakash S.; Angadi, Naveen; Chikkamath, Vijayalakshmi (International Journal of Advances in Medicine, 2018)
Background: Metabolic syndrome and its individual criteria pose a risk for atherosclerosis and cardiovascular disease (CVD). Carotid intima media thickness (CIMT) is a well-known marker of subclinical atherosclerosis. This study was aimed to assess CIMT in patients with metabolic syndrome. Methods: This one year cross-sectional study was conducted in the Department of Medicine, KLES Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi from January 2016 to December 2016. A total of 100 patients diagnosed to have metabolic syndrome based on national cholesterol education program adult treatment panel III (NCEP ATP III) criteria were studied. All the patients were subjected to carotid B mode ultrasonography. Results: The most common age group was 51 to 60years (29%). Out of 100 individuals who were diagnosed to have metabolic syndrome, 60% had five criteria, 29% had four criteria and 3% had three criteria. Most of the of the individuals (61.00%) had normal (≤0.10cms) CIMT while high (>0.10cm) levels were noted in 39.00% of the individuals. The mean CIMT was noted as 0.13±0.16cms. The mean SBP (150.15±10.39 vs 142.98±20.09mmHg; p=0.042), DBP (94.51±6.53 vs 90.16±9.91 mmHg; p=0.017), total cholesterol levels (243.53±65.74 vs 195.95±29.8 mg/dL; p<0.001) and triglyceride levels (221.07±48.44 vs 180.85±24.74mg/dL; p <0.001) were noted in individuals with raised CIMT compared to individuals with normal CIMT. Majority of the individuals had abnormal HDL (93.00%) and 41.94% of the individuals with abnormal HDL had raised CIMT (p=0.027). Conclusions: Some individuals with metabolic syndrome are likely to have raised CIMT. The rise in CIMT among the patients with metabolic syndrome is associated with raised SBP, DBP, abnormal HDL (specifically in males), total cholesterol and triglycerides.